2010
DOI: 10.1111/j.1360-0443.2010.02999.x
|View full text |Cite
|
Sign up to set email alerts
|

Were the changes to Sweden's maintenance treatment policy 2000–06 related to changes in opiate‐related mortality and morbidity?

Abstract: The liberalization of Sweden's drug policy correlated with an increase in maintenance treatment, a decrease in opiate-related mortality and inpatient care and an increase in deaths with methadone and buprenorphine in the tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 10 publications
4
32
0
Order By: Relevance
“…It also induces tolerance to opioids,19 20 and a corresponding decline in drug-related morbidity including overdoses should be expected. Some studies report improved somatic health during OMT based on interviews,17 clinical assessment21 and reduced consumption of inpatient care due to infections,22 23 but relatively few studies have investigated OMT-related somatic health effects and morbidity patterns. In a previous study we found reductions in somatic disease incidents treated in hospital or by general practitioners during OMT compared to ‘not in treatment’ 24.…”
Section: Introductionmentioning
confidence: 99%
“…It also induces tolerance to opioids,19 20 and a corresponding decline in drug-related morbidity including overdoses should be expected. Some studies report improved somatic health during OMT based on interviews,17 clinical assessment21 and reduced consumption of inpatient care due to infections,22 23 but relatively few studies have investigated OMT-related somatic health effects and morbidity patterns. In a previous study we found reductions in somatic disease incidents treated in hospital or by general practitioners during OMT compared to ‘not in treatment’ 24.…”
Section: Introductionmentioning
confidence: 99%
“…The powerful dependence liability of heroin and intense craving for the drug makes successful rehabilitation a difficult problem [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant increase in mortality specifically related to buprenorphine and methadone also occurred. 51 …”
Section: Misuse Abuse and Diversion Of Buprenorphinementioning
confidence: 99%